2012
DOI: 10.1152/ajpendo.00411.2011
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent renal cortical microvascular loss in female mice

Abstract: LO. Age-dependent renal cortical microvascular loss in female mice. Am J Physiol Endocrinol Metab 302: E979 -E986, 2012. First published February 7, 2012 doi:10.1152/ajpendo.00411.2011.-Renal function and blood flow decline during aging in association with a decrease in the number of intrarenal vessels, but if loss of estrogen contributes to this microvascular, rarefaction remains unclear. We tested the hypothesis that the decreased renal microvascular density with age is aggravated by loss of estrogen. Six-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Similarly, the first reported observation of murine ochronosis was in a tyrosinemic mouse with extensive kidney damage 14. As age-related loss of renal function normally occurs in humans (beginning in the fourth decade)22 and mice,23 declining excretion in the ageing kidney may lead to rising plasma HGA concentration, co-incident with the midlife observation of pathological, ochronotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the first reported observation of murine ochronosis was in a tyrosinemic mouse with extensive kidney damage 14. As age-related loss of renal function normally occurs in humans (beginning in the fourth decade)22 and mice,23 declining excretion in the ageing kidney may lead to rising plasma HGA concentration, co-incident with the midlife observation of pathological, ochronotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with previous literature studying age-dependent progression of renal damage in female mice. Urbieta-Caceres et al suggested that aging-induced renal interstitial fibrosis in female mice was mediated by loss of endogenous estrogen [ 30 ]. Zheng et al reported that female mice developed progressive glomerulosclerosis after menopause [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smaller arterioles and capillaries are the first to suffer a vascular dropout when facing acute or chronic insults and the lost of MV circulation via structural rarefaction has been shown to have an impact on renal hemodynamics (5, 81, 127) and function (103, 131). Furthermore, it has been shown that renal MV structural rarefaction plays an important role in the reduction of RBF and GFR with normal aging (149), indicating that vascular regression is also a physiological event.…”
Section: Rarefaction: Definition MV Rarefaction and The Kidneymentioning
confidence: 99%